Macroevolutionary trends in the genus Torvoneustes (Crocodylomorpha: Metriorhynchidae) and discovery of a giant specimen from the Late Jurassic of Kimmeridge, UK. Issue 2 (17th October 2019) - Young, Mark T; Foffa, Davide; Steel, Lorna; Etches, Steve
Abstract: The metriorhynchid crocodylomorph fauna of the Late Jurassic Kimmeridge Clay Formation (KCF) of the UK was highly diverse. One genus from this Formation, Torvoneustes, was unique in evolving dentition similar to known chelonivorous crocodylomorphs and enlarged attachment sites for the pterygoideus adductor musculature. Here we report the largest known Torvoneustes specimen, the occipital region of a large cranium that was discovered on the shore of Brandy Bay, Dorset, UK (KCF). We also report three tooth crowns discovered during the 19 th century from Oxfordshire that can also be referred to Torvoneustes . The partial braincase is unique in having: verticalized basioccipital tuberosities that have thickened ventral margins, the notch between the basioccipital tuberosities is a narrow inverted 'U'-shape and a subrectangular-shaped carotid canal foramina. The presence of 'occipital fossae' (deep concavities with the hypoglossal foramina in their dorsomedial corners) and carotid foramina with raised rims relative to the basioccipital posterior surface, allow us to refer it to Torvoneustes . Although incomplete, the exceptional size of the specimen demonstrates that Torvoneustes attained larger body lengths than previously supposed (3.7–4.7 m). Comparing the dimensions of this specimen to other metriorhynchids suggests that at least some Torvoneustes specimens rivalled Plesiosuchus manselii in body length.